2017
DOI: 10.1021/acs.est.6b05736
|View full text |Cite
|
Sign up to set email alerts
|

pH of Aerosols in a Polluted Atmosphere: Source Contributions to Highly Acidic Aerosol

Abstract: Acidity (pH) plays a key role in the physical and chemical behavior of PM. However, understanding of how specific PM sources impact aerosol pH is rarely considered. Performing source apportionment of PM allows a unique link of sources pH of aerosol from the polluted city. Hourly water-soluble (WS) ions of PM were measured online from December 25th, 2014 to June 19th, 2015 in a northern city in China. Five sources were resolved including secondary nitrate (41%), secondary sulfate (26%), coal combustion (14%), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
134
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 60 publications
21
134
5
Order By: Relevance
“…The studies using the standard ISORROPIA model with the stable state assumption have predicted unrealistic pH values of around 7 and should be reevaluated He et al, 2017). Previous ISORROPIA calculations using the metastable state assumption 15 obtained average pH values from 4.1 to 5.4 (He et al, 2017;Liu et al, 2017a;Shi et al, 2017;Cheng et al, 2016;Guo et al, 2017b;Tan et al, 2018), agreeing reasonably with our results (an average pH value of 4.6). It is noted that concentrations of Ca 2+ and Mg 2+ were not measured in this study and a sensitivity test suggests that including these crustal cations in thermodynamic calculations would increase predicted pH values by about 0.1 unit (Fig.…”
Section: Summary Of Existing Studiessupporting
confidence: 89%
“…The studies using the standard ISORROPIA model with the stable state assumption have predicted unrealistic pH values of around 7 and should be reevaluated He et al, 2017). Previous ISORROPIA calculations using the metastable state assumption 15 obtained average pH values from 4.1 to 5.4 (He et al, 2017;Liu et al, 2017a;Shi et al, 2017;Cheng et al, 2016;Guo et al, 2017b;Tan et al, 2018), agreeing reasonably with our results (an average pH value of 4.6). It is noted that concentrations of Ca 2+ and Mg 2+ were not measured in this study and a sensitivity test suggests that including these crustal cations in thermodynamic calculations would increase predicted pH values by about 0.1 unit (Fig.…”
Section: Summary Of Existing Studiessupporting
confidence: 89%
“…During the less polluted period, average concentrations of SO 4 2− (8.9 μg/m 3 in episode A) were higher than those of NO 3 − (6.2 μg/m 3 in episode A), while over the entire period, average concentrations of SO 4 2− (11 μg/m 3 ) were lower than those of NO 3 − (13 μg/m 3 ). Our previous work also showed that when sulfate was dominant, pH could be low (<4; Shi et al, 2017).…”
Section: 1029/2018jd029976mentioning
confidence: 79%
“…In this work, x ij is the measured concentration of the j th WS ions in the i th sample, f pj is the concentration of the j th WS ions in p th source, and g ip is the contribution of p th source to TWI for the i th sample. More detailed information can be found in our previous works (Shi et al, ) and the supporting information.…”
Section: Methodsmentioning
confidence: 99%
“…can predict H + , ALWC, and partitioning of volatile/semi volatile components, such as 65 ammonia (Fountoukis and Nenes, 2007;Clegg et al, 2008). These models' ability to describe physiochemical properties of airborne particles was validated by various studies Guo et al, 2016;Shi et al, 2017;Tao and Murphy, 2019;Murphy et al, 2017). However, several publications using the same method gave https://doi.org/10.5194/acp-2019-541 Preprint.…”
Section: Introductionmentioning
confidence: 99%